Spiritual Leadership and Pedagogical Competence: Enhancing the Quality of Student Services in an Islamic Boarding School - Asep Sopian; Diding Nurdin; Nani Hartini (Educazione: Journal of Education and Learning, 2026)
The quality of student services in Islamic boarding schools depends on two forces working together: the principal's spiritual leadership and teachers' pedagogical competence. How the first actually strengthens the second in daily practice remains underexplored. This study examines that relationship at SMP Daarut Tauhiid Boarding School Putra in Bandung. The research employed a qualitative approach with a single case study design. Data came from in-depth interviews with four key informants: the principal and the vice principals for curriculum, student affairs, and dormitory coaching. Participant observation and document analysis complemented these interviews. The data were analysed through an interactive thematic model, and trustworthiness was established through source and method triangulation and member checking. Four themes emerged. First, spiritual leadership manifests through exemplary conduct (uswah hasanah), value-based vision communication, and divine accountability (mas'uliyyah ilahiyyah) as its motivational foundation. Second, pedagogical competence is strengthened through coaching-based supervision, weekly teacher upgrading, and a digital monitoring system. Third, these elements jointly produce holistic improvements in student service quality across the academic, character, and spiritual dimensions. Fourth, the process is shaped by identifiable supporting and inhibiting factors. The study shows that transcendent accountability and data-driven instructional management can reinforce rather than undermine one another. Spiritual leadership thus becomes a catalyst for transformative education and learning, in which strengthening pedagogical competence drives the moral, spiritual, and academic growth of teachers and students alike.